(untitled) (Delta Medical College Journal, 2018)
Background: Cardiac myxoma is the most common benign cardiac tumour, accounting for more than half of all primary cardiac tumours. Most myxomas are sporadic and the cause is largely unknown. Familial variants with an autosomal dominant inheritance exist. It is localized generally in the left atrium and typically develops in females. Clinical manifestations can mimic cardiac conditions and depend on the natural behaviour of the tumour and its location within the heart, ranging from being completely asymptomatic to causing sudden death. Establishing an early diagnosis is essential, which is confirmed by histopathology. Objective: The aim was to find the relation between cardiac myxomas with age, sex and cardiac sites. Materials and method: This cross sectional study was done in the pathology department of Delta Hospital Limited, Dhaka, Bangladesh, during the period of January 2014 to July 2016. A total of 24 cases were studied irrespective of age, sex along with clinical diagnosis. Results: Among the study subjects females were predominant (70.83%) and highest frequency of cases occurred in between 41-50 years of age (41.67%). Commonest site was left atrium (83.33%). Conclusion: The present study revealed that cardiac myxoma occurs most commonly in the 5th decade with female predominance and the most common site is left atrium. Delta Med Col J. Jan 2018 6(1): 4-8